2018
DOI: 10.3168/jds.2017-14250
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of milk ELISA scores as an indicator of Johne's disease (paratuberculosis) in dairy cattle

Abstract: Johne's disease (or paratuberculosis), caused by Mycobacterium avium ssp. paratuberculosis (MAP) infection, is a globally prevalent disease with severe economic and welfare implications. With no effective treatment available, understanding the role of genetics influencing host infection status is essential to develop selection strategies to breed for increased resistance to MAP infection. The main objectives of this study were to estimate genetic parameters for the MAP-specific antibody response using milk ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 58 publications
1
29
0
1
Order By: Relevance
“…Expression of ZBTB20 has been observed in human tissues relevant to Johne's disease, such as the colon, duodenum, lymph nodes, small intestine, and spleen (Fagerberg et al, 2014). Moreover, ZBTB20 was also identified as a candidate gene in the genome-wide association study conducted by Brito et al (2018) in dairy cows, further substantiating the evidence that ZBTB20 could indeed be associated with the resistance status of cattle to MAP.…”
Section: Zbtb20mentioning
confidence: 58%
See 3 more Smart Citations
“…Expression of ZBTB20 has been observed in human tissues relevant to Johne's disease, such as the colon, duodenum, lymph nodes, small intestine, and spleen (Fagerberg et al, 2014). Moreover, ZBTB20 was also identified as a candidate gene in the genome-wide association study conducted by Brito et al (2018) in dairy cows, further substantiating the evidence that ZBTB20 could indeed be associated with the resistance status of cattle to MAP.…”
Section: Zbtb20mentioning
confidence: 58%
“…Furthermore, the rho kinase signal pathway has previously been implicated in inflammatory bowel disease (IBD) in humans, playing roles in intestinal barrier damage, abnormal immune response, and intestinal fibrosis (Huang et al, 2015). Brito et al (2018) also identified KALRN as a candidate gene in an independent population of ELISA-tested Canadian Holstein cattle. Thus, it is not unrealistic to hypothesize that KALRN plays an important role in the aforementioned processes in cattle susceptible to Johne's disease.…”
Section: Candidate Genes Associated With Humoral Response To Mapmentioning
confidence: 89%
See 2 more Smart Citations
“…As recently reviewed by Brito et al [6], various studies have shown the role of host genetics in resistance to MAP and have estimated heritability values for this trait between 0.03 and 0.27. In addition, numerous genomewide association studies (GWAS) have been conducted using genotyping of single-nucleotide polymorphisms (SNPs) at low [7], medium [8][9][10][11][12][13][14], or high [6,15,16] densities as well as whole-genome sequences [17,18] imputed from data of the 1000 Bull Genomes project [19]. These GWAS analyses have led to the identification of quantitative trait loci (QTL) associated with resistance/susceptibility to MAP on all Bos taurus (BTA) autosomes, with the most frequently identified QTL located on BTA1, 6, 7, and 23.…”
mentioning
confidence: 99%